MORPHOLOGICAL RESPONSE TO IMPLANTATION OF A POLYPROPYLENE MESH WITH A PRF MEMBRANE IN PATIENTS WITH POSTOPERATIVE VENTRAL HERNIA AND UNDIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA - Piatnochka, V. I.; Prodan, A. M. (International Journal of Medicine and Medical Research, 2019)
Background. Current herniology promotes the widespread usage of mesh implants in the primary treatment and, especially, in the for postoperative ventral hernias. Objective. The aim of the research was to study the morphological response of the tissues of muscular aponeurotic layer to implantation of a polypropylene mesh with using PRF membrane-enriched platelets in the patients with postoperative ventral hernia and concomitant undifferentiated dysplasia of connective tissues. Methods. The research involved 98 patients with postoperative ventral hernia, who underwent retro-muscular alogernioplasty by the Sublay technique of implantation of ‘light’ meshes, and a ‘light’ polypropylene mesh (PPM) in combination with a platelet-rich fibrin (PRF) membrane. The patients were divided into experimental groups according to the presence of undifferentiated connective tissue dysplasia syndrome. Results. Microscopic studies carried out after the implantation of a polypropylene mesh with a PRF membrane has proved that structural changes in connective tissues are like those of a polypropylene mesh, but they are less significant. There was a leukocyte infiltration near the mesh material, but its area was small. The enlargement and blood filling of the vessels of microcirculatory channel was a manifestation of the increased vascularization of this area. Conclusions. The usage of a polypropylene mesh in combination with a PRF membrane in the surgical treatment of postoperative ventral hernias reduces inflammatory changes in the tissues significantly and increases the activation of fibroblasts and signs of collagen fibers around the mesh material that is relevant especially for the patients with connective tissue pathology.